Peri‑urbanization and sustainability of a groundwater resource - Mohd Khairul Amri, Kamarudin; Sunardi, Sunardi; Miranti, Ariyani (2020)
In developing countries, such as Indonesia, urbanization equates to industrialization. To actuate rapid economic development, the government generally puts in place strong policies to transform rural into industrialized peri-urban/urban areas. This triggers a number of environmental problems, one of which is the degradation of groundwater resources. This study aimed to investigate whether rural to urban transformation caused such environmental degradation. We selected the Majalaya District, a typical peri-urban area of Bandung Metropolitan, where rapid industrialization, mainly related to the textile industry, is taking place. This research adopted a water balance analysis applied to a shallow groundwater resource, contrasting supply with demand after 9 years of development (2005–2014). Data concerning water supply and demand were collected from relevant stakeholders, except for water consumption by vegetation and agricultural land use. For the latter, GIS and QuickBird image analysis were conducted. The results indicate that the industrial development in Majalaya has caused a groundwater crisis. A nine-year period of fast-growing number of industries has caused water defcit, which was also intensifed by the rate of land conversion.